2021
DOI: 10.1002/ehf2.13497
|View full text |Cite
|
Sign up to set email alerts
|

Integrins in cardiac hypertrophy: lessons learned from culture systems

Abstract: Heart growth and pathological changes are accompanied by extracellular matrix-dependent alterations in integrins and integrin-associated proteins, suggesting their role in heart development and disease. Most of our knowledge on the involvement of integrins in heart pathology is provided by the in vivo experiments, including cardiac hypertrophy models. However, in vivo studies are limited by the complex organization of heart tissue and fail to discern cell types and particular integrins implicated in hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 85 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…First, Piezo1 can be activated by increased membrane tension 32,33 , which might reasonably be expected due to increased membrane forces associated with pressure overload. Force could also be transduced to the Piezo1 channel via cytoskeletal tethers or crosstalk with proteins that link the cardiomyocyte to the extracellular matrix, such as integrins, many of which have been implicated in the development of cardiac hypertrophy [46][47][48] . Our studies of ventricular myocytes from multiple organisms suggest localization of both Piezo1 and TRPM4 to the T-tubular system 19 .…”
Section: Discussionmentioning
confidence: 99%
“…First, Piezo1 can be activated by increased membrane tension 32,33 , which might reasonably be expected due to increased membrane forces associated with pressure overload. Force could also be transduced to the Piezo1 channel via cytoskeletal tethers or crosstalk with proteins that link the cardiomyocyte to the extracellular matrix, such as integrins, many of which have been implicated in the development of cardiac hypertrophy [46][47][48] . Our studies of ventricular myocytes from multiple organisms suggest localization of both Piezo1 and TRPM4 to the T-tubular system 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The ECM represents a major regulator of intercellular processes in cardiac cells, in addition to providing integrity and mechanical support, responsible for functional and phenotypic changes ( Bildyug, 2021 ). After birth, the heart undergoes extensive alterations in the ECM composition and structure to adapt to physiological requirements of the growing body.…”
Section: The Extracellular Matrix Of the Heartmentioning
confidence: 99%
“…Major works on integrins role are mostly focused on development and disease using in vitro models. In cardiomyocytes, the main integrins are α 1 β 1 , α 5 β 1 , and α 7 β 1 , which are receptors for mainly collagen, fibronectin, and laminin, and these integrins are dynamically regulated during development ( Bildyug, 2021 ). For example, cardiomyocyte integrins β 1D and β 1A are co-expressed in heart of E11 embryos, but the expression of β 1A declines as β 1D increases until it becomes the only β 1 isoform present in cardiomyocytes a few days after birth ( Brancaccio et al, 1998 ; Meagher et al, 2021 ).…”
Section: The Extracellular Matrix Of the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, FAs have an essential position in regulation of the biological behaviors of cells and play a key role in human health and disease. A large number of studies have revealed the important role of FAs in the initiation and progression of cancers, such as prostate cancer, breast cancer, hepatocellular carcinoma, and glioblastoma 9 , hematologic disorders 10 , kidney diseases 11 , neurodegenerative diseases 12 , cardiovascular diseases 13 , digestive system diseases 14 and metabolic diseases 15 . Recently, increasing evidence reports that FA proteins can regulate the biological behaviors of cells, and participate in the damage and repair of tissues in skeletal system 16 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%